Economic Development Mechanisms of Innovative Services in Bukhara Hotels - Istamkhuja Olimovich Davronov (Garuda Prestasi Nusantara Consulting, 2021)
The the article focuses on the development of economic mechanisms for innovative services in Bukhara hotels, the use of foreign experience and the wide range of measures implemented in our country. The development of new innovative services in Bukhara hotels and their effective use will focus on the prospects of tourism development in the region. In addition, the analysis and comments on the economic performance of new innovative services in hotels, the importance of innovative new smart communications, subsidies for businesses operating in the hotel industry, measures taken to attract tourists to hotels. The article examines the best practices of foreign countries through the method of analysis of hotel development. Official statistics on the use of innovative services in the hotel sector were used. Methods of hotel development were analyzed on the example of countries around the world with many years of experience in the development of innovative types of services in the hotel industry. The policy of active innovative services in hotels, the use of innovative smart technologies in the industry and the application of experience in the training of qualified hotel staff in accordance with the economy of the region's hotels. The scientific article examines the relationship between the types of services in hotels and the potential of hotels with infrastructure facilities and their effective use. Today we are talking about the organization of the only